Supramolecular polyrotaxane-based nano-theranostics enable cancer-cell stiffening for enhanced T-cell-mediated anticancer immunotherapy - Haifen Luo; Jingqi Lv; Peiye Wen; Shan Zhang; Wen Ma; Zhen Yang (Nature Communications)
Abstract Despite the tremendous therapeutic promise of activating stimulators of interferon genes (STING) enable to prime robust de novo T-cell responses, biomechanics-mediated immune inhibitory pathways hinder the cytotoxicity of T cells against tumor cells. Blocking cancer cell biomechanics-mediated evasion provides a feasible strategy for augmenting STING activation-mediated anti-tumor therapeutic efficacy. Here, we fabricate a redox-responsive Methyl-β-cyclodextrin (MeβCD)-based supramolecular polyrotaxanes (MSPs), where the amphiphilic diselenide-bridged axle polymer loads MeβCD by the host-guest interaction and end-caping with two near-infrared (NIR) fluorescence probes IR783. The MSPs self-assemble with STING agonists diABZIs into nanoparticles (RDPNs@diABZIs), which enable simultaneous release of MeβCD and diABZIs in the redox tumor microenvironment. After the released diABZIs activate STING on antigen-presenting cells (APCs), de novo T-cell responses are initiated. Meanwhile, the released MeβCD depletes membrane cholesterol to overcome cancer-cell mechanical softness, which enhances the CTL-mediated killing of cancer cells. In the female tumor-bearing mouse model, we demonstrate that RDPNs@diABZIs lead to effective tumor regression and generate long-term immunological memory. Furthermore, RDPNs@diABZIs can achieve significant tumor eradication, with these mice remaining survival for at least 2 months.